Unusual Morphology of the Axillary Vein Forming a Loop around the Lateral Thoracic Artery. - Sudarshan S; Naveen K; Srinivasa RS; Venu MN (Department of Surgery, UKM Medical Centre, 2014)
Venous anomalies of the upper limb are not uncommon. However, unusual anomaly of the axillary vein forming a loop around a branch of the axillary artery has seldom been reported in the literature. In the present case, we report a rare case of perforation of the axillary vein (AV) by the lateral thoracic artery in the right axilla. It was noted in an approximately 65-year-old male cadaver of South Indian origin, during regular laboratory teaching to the medical undergraduates. The formation and termination of AV were found to be normal. The knowledge about the occurrence of the possible anomalies of AV is clinically important to avoid complications during the invasive therapeutic surgical procedures. It is also important during the diagnostic procedures such as ultrasound imaging and venography.